Educação para a igualdade de gênero: desafios e perspectivas da ação docente na UEB Moranguinho - SOUZA , Letícia Régia Gomes (2021)
This dissertation talk about Education for gender equality in the teaching action of male and female teachers. It aims to investigate the challenges and perspectives that male and female teachers and teachers face to develop an education in a perspective of gender equality between boys and girls, with a view to building a Book of Pedagogical Guidelines on the subject. It is a qualitative research of the action research type in interface with the critical-dialectical framework. As research participants we have a manager, a pedagogical coordinator and three teachers of the 1st year of Elementary School. We use the seminar as a research technique, for the mobilization and engagement of collaborators; and as data collection instruments we used semi-structured interviews. We used Content Analysis as a technique for interpreting the collected data. We found, with the support of the research collaborators, that the lack of inclusion of Gender and Diversity studies in Teacher Education; the conception of the parents; Cultural issues and Prejudice against Women are the main challenges that teachers and teachers face to develop an Education for Gender Equality. As well, dialogue and continuing education are the pedagogical strategies that will help teachers to face prejudice, discrimination and gender violence between girls and boys. The results of this investigation present indications for the urgency of the inclusion of the theme in the initial training courses of Pedagogy and the licentiates, as well as in the continuing education courses. It is worth mentioning that the findings perceived in the interviews were decisive for the construction of the themes discussed in the seminars held, because, in addition to valuing the listening that the data revealed, we also prioritized focusing on propositions that broke with the fear of working with gender relations, due to the lack of specific training. In view of the findings, we collaboratively build a Book of Pedagogical Guidelines in order to contribute to the inclusion of gender relations in teaching activities, in the fight against prejudice and gender inequality in the school context.